La piedad divina. Desde el paganismo hasta el Cristianismo - Konstan, David (Centro de Estudios Latinos. IdIHCS - CONICET. Facultad de Humanidades y Ciencias de la Educación. Universidad Nacional de La Plata, 2007)
The concept of divine mercy has gone through different stages throughout its evolution, but the conceptions of Christian religion and pagan religion do not always oppose themselves. This paper examines philosophic (Aristotle, Hellenistic philosophy), literary (Sophocles, Homer) and epigraphical sources (with their varied meanings, sometimes temporarily overlapped), as well as the use of the concept in pagan prayers and official petitions. Although Stoic rationalism considers mercy as incompatible with knowledge and justice, the Christian Lactantius retrieves the value of properly used passions, striking a signpost in converting a pagan emotion into a Christian virtue and duty